آفاق استخدام الطاقة المتجددة في قطاع النقل لدعم استدامته مع الإشارة إلى تجربة: الصين ومحاولة تكييفها مع حالة الجزائر - نسيمة لعرج مجاهد; فاطمة الزهراء مغبر (My University, 2014)
يعتبر قطاع النقل من القطاعات الناهضة بالاقتصاد الوطني، وواحدا من القطاعات الأكثر تحديا فيما يتعلق بمكافحة التغيرات المناخية الواضحة التي يشهدها العالم، وبضمان أمن الطاقة، وتشير التوقعات إلى ان الطلب العالمي على مصادر الطاقة اللازمة لقطاع النقل خلال العشرين سنة القادمة ستفوق الطلب على الطاقة في قطاعات الاستهلاك الأخرى. لذلك أصبح لزاما التوجه إلى ترشيد استخدامات الطاقة في قطاع النقل لتحقيق التنمية المستدامة من خلال ادماج الطاقة البديلة النظيفة التي لا تنضب بأشكالها المتعددة في قطاع النقل. وعليه تهدف هذه الورقة البحثية الى ايجاد منهجيات لتطوير نظم النقل المستدامة في المستقبل من خلال الاشارة الى استراتيجيات كل من الصين في هذا المجال ومحاولة تكييفا مع حالة الجزائر، وقد خلصت الورقة البحثية الى استنتاج مفاده أن النقل المستدام لا يمكن أن يتطور بشكل كامل دون تنفيذ نظام شامل يعتمد على ادماج الطاقة المتجددة في هذا القطاع، وان استراتيجيات تطوير النقل الحالي ليست كافية وهناك حاجة إلى المزيد من المبادرات لتحقيق الاستقرار في الطلب على الطاقة في قطاع النقل. Abstract: The transportation sector is a major component of our national economy, and one of the most challenging sectors in terms of combating climate change and ensuring energy security. Forecasts indicate that the global demand of the required energy sources for the transport sector over the next twenty years will exceed the demand of energy in other sectors of consumption. Thus, guidance becomes necessary towards the rationalization of energy consumption in the transport sector to achieve sustainable development through the integration of alternative clean inexhaustible energy in its multiple forms in the transport sector. This research paper seeks to contribute to the development of methodologies to identify and develop future sustainable transport systems as well as to apply methodologies of other countries such as: China and try to adapt with the case of Algeria. The research paper has concluded that transport cannot be fully developed without implementing an overall renewable energy system, and the current transport development strategies are not sufficient and more initiatives are needed to realize the energy demand of the transport sector.
Keywords: النقل، التنمية المستدامة، الطاقات المتجددة، الصين، الجزائر